Effects of Annealing Temperature on Co30Cu70 Mechanical Alloys - RATTANASAKULTH, Watcharee; SIRISATHITKUL, Chitnarong (Walailak Journal of Science and Technology (WJST), 2011)
Physical properties of Co30Cu70 mechanical alloys prepared by ball milling were investigated. After milling for 50 h, the powder contained Co-rich, Cu-rich clusters as well as Co-Cu solid solution. Annealing at 200 - 300 °C for 30 min modified thermal behaviors but only slightly affected magnetic properties. Higher temperature annealing (400 - 500 °C) led to substantial oxidation of Co and Cu and deteriorated magnetic properties. Pressed Co30Cu70 pellets exhibited 0.6 - 2 % giant magnetoresistance (GMR) but showed modest GMR after heat treatment. GMR disappeared by annealing at 500 °C as large fractions of Co and Cu were converted into oxides.